Benchmarking of Governmental Support Measures for University-Industry Cooperation - Rõigas, Kärt; Seppo, Marge; Varblane, Urmas (Estonian Discussions on Economic Policy, 2013)
This paper aims to benchmark Estonian governmental support measures targeted toward enhancing university-industry collaboration to European best practice and make suggestions for the development of these measures. The intensity and scope of university-industry cooperation support measures varies heavily in Europe. The survey of European University-Business Cooperation, Pro Inno Europe and Erawatch database of policy measures, and Community Innovation Survey reveal that Finnish, German and Austrian support systems are best balanced and provide good university-industry cooperation intensity. The cooperation measures in Estonia are weak and improvement should be made by increasing the Estonian governmental funding, mandatory cooperation in support measures, networking and applied research in universities, on-going application possibilities, reducing the bureaucracy, and improving the timing of measures.